Gender Differences on Stress and Coping Strategies Among Faculty of a University - Lycel L. Pacheco; Jirec A. Bacongco; Noel M. Dayono; Mary Ann S. Dagunan (East Asian Journal of Multidisciplinary Research, 2024)
The results indicate that there is no notable variance in the levels of depression, anxiety, and stress among faculty members when categorized by age, gender, and marital status. Additionally, the study reveals a positive correlation between depression, anxiety, and stress with emotion-focused coping and avoidant coping strategies. In other words, as the severity of depression, anxiety, and stress increases among teachers, so does their reliance on emotion-focused coping and avoidant coping mechanisms. However, the study found that the distinction between genders in this regard was not significant.. The research suggests, among other things, that faculty members should undergo retesting to assess the reliability of the results. Despite the minimal gender differences, some individuals are still facing significant levels of depression, anxiety, and stress. This reaffirmation of the initial findings should be submitted to the Human Resource Management Office to support the development of a wellness program.